Fast growing research on negative emissions. (1st March 2017) - Minx, Jan C; Lamb, William F; Callaghan, Max W; Bornmann, Lutz; Fuss, Sabine
Abstract: Generating negative emissions by removing carbon dioxide from the atmosphere is a key requirement for limiting global warming to well below 2 °C, or even 1.5 °C, and therefore for achieving the long-term climate goals of the recent Paris Agreement. Despite being a relatively young topic, negative emission technologies (NETs) have attracted growing attention in climate change research over the last decade. A sizeable body of evidence on NETs has accumulated across different fields that is by today too large and too diverse to be comprehensively tracked by individuals. Yet, understanding the size, composition and thematic structure of this literature corpus is a crucial pre-condition for effective scientific assessments of NETs as, for example, required for the new special report on the 1.5 °C by the Intergovernmental Panel on Climate Change (IPCC). In this paper we use scientometric methods and topic modelling to identify and characterize the available evidence on NETs as recorded in the Web of Science. We find that the development of the literature on NETs has started later than for climate change as a whole, but proceeds more quickly by now. A total number of about 2900 studies have accumulated between 1991 and 2016 with almost 500 new publications in 2016. The discourse on NETs takes place in distinct communities around energy systems, forests as well as biochar and other soil carbon options. Integrated analysis of NET portfolios—though crucial for understanding how much NETs are possible at what costs and risks—are still in their infancy and do not feature as a theme across the literature corpus. Overall, our analysis suggests that NETs research is relatively marginal in the wider climate change discourse despite its importance for global climate policy.